2013
DOI: 10.1371/journal.pone.0056052
|View full text |Cite
|
Sign up to set email alerts
|

Musical Expertise and the Ability to Imagine Loudness

Abstract: Most perceived parameters of sound (e.g. pitch, duration, timbre) can also be imagined in the absence of sound. These parameters are imagined more veridically by expert musicians than non-experts. Evidence for whether loudness is imagined, however, is conflicting. In music, the question of whether loudness is imagined is particularly relevant due to its role as a principal parameter of performance expression. This study addressed the hypothesis that the veridicality of imagined loudness improves with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 72 publications
(127 reference statements)
4
24
0
2
Order By: Relevance
“…In terms of the main hypotheses we found that, musical practice was positively related to VMI pitch ability, as was expected. This finding is consistent with the VMI pitch results found by Aleman et al (2000) and is aligned with the findings of increased VMI loudness accuracy in experts reported by Bishop et al, (2013). The present study also extends the work by Aleman et al (2000) to include a real time VMI pitch listening task,…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of the main hypotheses we found that, musical practice was positively related to VMI pitch ability, as was expected. This finding is consistent with the VMI pitch results found by Aleman et al (2000) and is aligned with the findings of increased VMI loudness accuracy in experts reported by Bishop et al, (2013). The present study also extends the work by Aleman et al (2000) to include a real time VMI pitch listening task,…”
Section: Discussionsupporting
confidence: 92%
“…By comparison, participants with musical practice experience made more appropriate distinctions between flat, sharp and unaltered pitch levels. Again, this result confirms the findings reported by Aleman et al (2000) and Bishop et al, (2013) regarding an association between VMI accuracy and musical expertise, but also provides the insight that non-musicians make more mistakes in a VMI task as they are unable to confirm when a pitch shift has occurred.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is conceivable that music students believe that they should be able to perform the manipulations, causing higher self-reported ability. But in past research, musical experts show better ability to complete similar imagery tasks in a lab setting (Bishop et al, 2013a;Herholz et al, 2008;Weir et al, 2015). Using self-reports instead of behavioral measures reflects a trade-off inherent in ecological assessment methods, which trade the ability to explore concepts in people's idiosyncratic, real-world environments for the control of lab-based methods.…”
Section: Discussionmentioning
confidence: 99%
“…Underground native sulfur can be mined by the Frasch process, which was successfully commercialized from 1902, by injecting superheated water. These sources of elemental sulfur were supposedly of fossil origin, produced by the action of Archaebacteria on sulfate deposits …”
Section: Introductionmentioning
confidence: 99%